Diversions, distractions, and privileges: consultation and the governance of mining in Nunavut. Issue 3 (2nd September 2019) - Scobie, Willow; Rodgers, Kathleen
Abstract: In the context of the growing global drive for mineral resources, Canada's northern territories have become a focal point for the rapid expansion of mineral extraction. Occurring within the terms of Canada's largest Indigenous land claim, the Nunavut Land Claim Agreement, the negotiation of Baffinland's Mary River Mine provides a case study of the dynamics of consultation within communities impacted by large-scale mining projects. Using Freudenburg's 2005 "privileged accounts" framework, our findings elucidate the power dynamics in the consultation processes between multinational mining corporations and Indigenous communities.